Self‐Healing Polyester Urethane Supramolecular Elastomers Reinforced with Cellulose Nanocrystals for Biomedical Applications - Zeimaran, Ehsan; Pourshahrestani, Sara; Kadri, Nahrizul Adib; Kong, Daniel; Shirazi, Seyed Farid Seyed; Naveen, Sangeetha Vasudevaraj; Murugan, S.S.; Kumaravel, T.S.; Salamatinia, Babak (John Wiley & Sons, 2019)
Stretchable self-healing urethane-based biomaterials have always been crucial for biomedical applications; however, the strength is the main constraint of utilization of these healable materials. Here, a series of novel, healable, elastomeric, supramolecular polyester urethane nanocomposites of poly(1,8-octanediol citrate) and hexamethylene diisocyanate reinforced with cellulose nanocrystals (CNCs) are introduced. Nanocomposites with various amounts of CNCs from 10 to 50 wt% are prepared using solvent casting technique followed by the evaluation of their microstructural features, mechanical properties, healability, and biocompatibility. The synthesized nanocomposites indicate significantly higher tensile modulus (approximately 36–500-fold) in comparison to the supramolecular polymer alone. Upon exposure to heat, the materials can reheal, but nevertheless when the amount of CNC is greater than 10 wt%, the self-healing ability of nanocomposites is deteriorated. These materials are capable of rebonding ruptured parts and fully restoring their mechanical properties. In vitro cytotoxicity test of the nanocomposites using human dermal fibroblasts confirms their good cytocompatibility. The optimized structure, self-healing attributes, and noncytotoxicity make these nanocomposites highly promising for tissue engineering and other biomedical applications.